Clinical profile and predictors of severity in children with scrub typhus admitted to paediatric intensive care unit - Aroor, Shrikiran; Mundkur, Suneel; Kumar, Sandeep (International Journal of Contemporary Pediatrics, 2023)
Background: Scrub typhus accounts for a significant portion of morbidity and mortality related to tropical infectious diseases. This study is done to determine the factors associated with complications and outcome in children with scrub typhus. Methods: It is a retrospective descriptive study conducted on children diagnosed with scrub typhus (IgM) admitted to the paediatric intensive care unit at a tertiary care centre in south India during 1 year of study period. Clinical profile, laboratory parameters, course of illness and outcome data were collected and analysed. Results: The study population included 88 children with scrub typhus. 32 children required intensive care unit admission. Remaining 56 children were included in non-severe scrub typhus group. Complications of scrub typhus included hepatic dysfunction (100%), pneumonitis 16 (50 %), meningoencephalitis 12 (37.5%), shock 12 (37.5%), acute respiratory distress syndrome (ARDS) 4 (12.5%), myocarditis 4 (12.5%), acute kidney injury (AKI) 2 (6.25%), multiple organ dysfunction syndrome (MODS) 2 (6.25%) and purpura fulminans 1 (3.1%). Mortality was observed in 2 (1.3%) children. It was found that anaemia and leucocytosis were predominantly associated with the risk of severe scrub typhus (odds ratio of 6.43 and 30.4 respectively, p value <0.001). Among other laboratory parameters, C-reactive protein (CRP) of >30 and hypoalbuminemia were significantly associated with mortality (p value <0.001). The median CRP and AST levels were significantly high in the severe scrub typhus group (p value 0.02 and 0.012 respectively). Conclusions: Hepatic dysfunction was present in all children admitted to PICU. Children with scrub typhus had an increased risk of developing complications in the presence of anaemia, leucocytosis, CRP>30 mg/l and severe hypoalbuminemia.